2017
DOI: 10.1016/j.jtumed.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Relation between ABO blood groups and obesity in a Saudi Arabian population

Abstract: Objectives ABO blood groups have been shown to be associated with different diseases. Very few studies have attempted to detect the association of ABO blood groups with obesity. The goal of this study is to find any potential relation between ABO blood groups and high body mass index (BMI) among a Saudi population, which may contribute to underlying genetic disorders. Methods A cross-sectional descriptive study was conducted using a structured questionnaire that contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Another study failed to link blood groups to obesity. 34 An earlier study that was conducted in the eastern region of Saudi Arabia estimated the frequency of ABO blood groups and its findings relate to the results of the present study. 5 The O blood group was determined to be the most prominent blood group in the current study (45%) and in the eastern region at large (51%).…”
Section: Discussionsupporting
confidence: 71%
“…Another study failed to link blood groups to obesity. 34 An earlier study that was conducted in the eastern region of Saudi Arabia estimated the frequency of ABO blood groups and its findings relate to the results of the present study. 5 The O blood group was determined to be the most prominent blood group in the current study (45%) and in the eastern region at large (51%).…”
Section: Discussionsupporting
confidence: 71%
“…A study done be Ahmed and colleagues [51] reported an increased prevalence of obesity in non-O individuals, while Smith et al (Smith et al, 2018) proved the exact opposite in his series. Awasaidi and colleagues reported no association between body mass index and the ABO system [52] . Despite these conflicting data, vascular inflammatory complications of obesity are definitely more abundant in non-O individuals.…”
Section: Iii-abo Grouping System and Affected Subgroups In Covid-19mentioning
confidence: 98%
“…Here we did not find any significant correlations between each ABO blood type either to the BMI or to the blood pressure. Previous study in Saudi Arabia and Ghana had reported that there was no correlation between the ABO blood grouping to the BMI (Alwasaidi et al 2017) or to the blood pressure (Abdollahi et al 2009). The ABO blood type is the method to determine the blood group of a person through the agglutination methods or molecular imprinting (Mujahid & Dickert 2015).…”
Section: Discussionmentioning
confidence: 94%